COVID 19 AND ITS EFFECTS ON HYPERTENSION FLUCTUATIONS IN IRAQI PATIENTS - Dr. Hijran Kamal salih Aldabbagh; Dr. Ali Sameer Hasan; Dr. Anwer Hameed Rashid (Scholar Express Journals, 2022)
COVID-19 is an infectious disease caused by the SARS-CoV-2 coronavirus, which more seriously affects patients of advanced ages and patients with immunodeficiency and chronic conditions, such as high blood pressure, and is of great importance in mortality from cardiovascular disease. vascular and cerebrovascular.This paper aims to know the effects of COVID-19 on hypertension fluctuations in Iraqi patientsThe retrospective study was conducted in one institution, different hospitals in Iraq, which is one of the main institutions for the care of patients with COVID-19 and 80 patients were collected and distributed into two groups, to 60 patients with hypertension and 20 patients as a control group,It was concluded in this study that arterial hypertension is a clinical indicator of its severity in COVID-19 patients, and the study shows patients with hypertension have a higher mortality rate and also a higher likelihood of complications (severe COVID-19, ARDS, need for ICU and disease progression) which also leads to higher healthcare costs
Keywords: COVID-19; ARDS; ICU; T2D